Evaluation of the Factors that Promote Improved Experience and Better Outcomes of Older Adults in Intermediate Care Setting - Blendell, Rona; Ojo, Omorogieva (J, 2020)
The aim of this article was to identify the main contributing factors to optimising improved experience and better outcomes for older adults participating in intermediate care setting. Background: Intermediate care is an integrated team intervention for patients experiencing an acute change in their function and well-being. Crisis intervention is one of several intermediate care pathways and provides a timely, person-centred, goal setting assessment to determine appropriate care and support for patients in the community. Method: This systematic review was conducted using key search terms and Boolean operators. A Critical Appraisal Skills Programme (CASP) tool was used to evaluate the studies and the data was extracted and synthesised systematically to develop themes relating to the research question. Results: Seven qualitative primary research studies and one mixed methods study were identified. The main themes were ‘communicating with patients’ and ‘patient participation’. Results showed neither themes are parallel entities but co-dependent. Patient-centred approaches to communication by professionals encouraged active patient participation, in turn optimising patient outcomes. Conclusion: This review showed that patient participation in intermediate care requires professionals using advanced communication skills and taking time to actively listen to what is important to the patients. In addition, poor professional communication resulted in passive patient participation. Implications for future practice are discussed.